Development of Mobile Robot System Based on Nano-scale Micro-surface Measurement. Issue 1 (1st January 2022) - Ji, Zhongwei; Wang, Pan; Jia, Jiahao; Ding, Yan; Zhao, Kang; Liu, Tingrui
Abstract: Absrtact. The system development of the mobile robot mainly includes two parts: one is to build a laser interference system based on piezoelectric ceramic dynamic carrier; The other part is the image processing of the interference fringe pattern collected by the interference system. The laser interference system can be installed on the front-end manipulator of the robot as an integral structure. The shape information of the measured micro-surface can be obtained by processing the interference fringes collected by the image acquisition card on the interference system, so as to achieve the purpose of high-precision surface roughness measurement.